1998
DOI: 10.1111/j.1151-2916.1998.tb02435.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Size Effects in a Barium Titanate Glass‐Ceramic

Abstract: A series of glass ceramics have been synthesized to produce bulk materials with nanometer-sized barium titanate (BaTiO 3 ) crystals grown in a residue glass matrix. Structureproperty relations have been made to determine the size distribution and the dielectric temperature dependence of the ceramics. Through dielectric and density mixing laws, it has been inferred that depolarization fields limit the dielectric polarizability of the particles and influence the transition temperature. The transition temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(117 citation statements)
references
References 29 publications
5
104
1
Order By: Relevance
“…However, these results are not in agreement with other reports where the critical size was estimated to be on the order of 10-20 nm. [16][17][18] Using the phenomenological Landau- found. However, the T C remains constant at 408 K for larger particles and the expected lowering of T C when the particle size approaches 30 nm was not observed.…”
Section: Introductionmentioning
confidence: 99%
“…However, these results are not in agreement with other reports where the critical size was estimated to be on the order of 10-20 nm. [16][17][18] Using the phenomenological Landau- found. However, the T C remains constant at 408 K for larger particles and the expected lowering of T C when the particle size approaches 30 nm was not observed.…”
Section: Introductionmentioning
confidence: 99%
“…9 In another study on BaTiO 3 , they did not see any shift in T m until the grain sizes were in submicron range. 10 Thus, changes in dielectric behavior of PMN-PZT þ PMnN and PMN-PZT þ MnO 2 will have some contribution from the 10X difference in grain size, but other factors are required to explain the overall variation. We did not observe any effect of frequency on the T max , which confirmed that the observed effects were related to composition not space charge polarization (Fig.…”
Section: -3mentioning
confidence: 99%
“…[36][37][38][39] Clearly, our results are in accordance with reports where the critical size of BaTiO 3 NPs was estimated to be on the order of 10-20 nm. 40 Moreover, the energy dispersive X-ray spectroscopy (EDS) microanalysis also substantiated the success in synthesizing PS-functionalized BaTiO 3 NPs (Fig. S4 †).…”
Section: 28mentioning
confidence: 81%